ANALYSIS OF IMMUNOHISTOCHEMICAL EXPRESSION OF EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) IN COLORECTAL CANCER - Sadaf, Ghazala; Khadim, Muhammad Tahir; Ahmed, Rabia; Asif, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate immunohistochemical expression of EGFR in colorectal cancer (CRC).Study Design: Descriptive cross sectional study.Place and Duration of Study: Histopathology Department, Armed Forces Institute of Pathology (AFIP), Rawalpindi, from Mar 2017 to Aug 2017.Methodology: A total of 100 cases of histologically confirmed CRC were retrieved from archive of Histopathology department, AFIP Rawalpindi. Patients’ age, gender, histologic type and grade were noted. Immunohistochemistry for EGFR was applied and results were recorded. Data was analyzed using SPSS version 22. Descriptive statistics, frequencies and percentages were calculated.Results: A total of hundred (n=100) patients were enrolled. Mean age of the study patients was 54.3 ± 16.3 years. The group of patients consisted of 68 (68%) men and 32 (32%) women. The majority of primary tumours were located in the rectum 39, (39%), followed by ascending colon 16 (16%), rectosigmoid junction 14 (14%), cecum 13 (13%), sigmoid colon 9 (9%), transverse colon 5 (5%) and descending colon 4 (4%). Most frequent histologic type was adenocarcinoma 80 (80%), followed by mucinous adenocarcinoma 12, (12%) and signet ring cell carcinoma 8 (8%). Most tumours were moderately differentiated 47 (47%), followed by well differentiated 34 (34%) and poorly differentiated 19 (19%). EGFR expression was found in 39 cases (39%). Among adenocarcinoma 41% (n=33/80) were EGFR positive and among mucinous adenocarcinoma 50% (n=6/12) were EGFR positive. All signet ring cell carcinoma cases were EGFR negative. Among well differentiated CRCs 41% (n=14/34) were EGFR positive, among moderately differentiated 40% (n=19/47) were EGFR positive and among poorly differentiated 46%(n=6/13) were EGFR positive.Conclusion: A significant percentage of CRC expressed EGFR but no statistically significant correlation was seen between EGFR expression and clinicopathological variables. Estimation of EGFR expression status may help to select the patients with CRC for targeted therapy, which is likely to improve the response rates.